2014
DOI: 10.1128/iai.00820-13
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium Biofilm Attenuates Mononuclear Phagocyte Function by Triggering Hyperstimulation and Apoptosis during Early Infection

Abstract: Mycobacterium avium subsp. hominissuis is an opportunistic human pathogen that has been shown to form biofilm in vitro and in vivo. Biofilm formation in vivo appears to be associated with infections in the respiratory tract of the host. The reasoning behind how M. avium subsp. hominissuis biofilm is allowed to establish and persist without being cleared by the innate immune system is currently unknown. To identify the mechanism responsible for this, we developed an in vitro model using THP-1 human mononuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 39 publications
0
65
0
2
Order By: Relevance
“…The ability of nontuberculous mycobacteria (NTM) to form biofilm creates challenges for treatment efficacy and host clearance (7, 8, 10, 11). We recently reported that NTM contain extracellular DNA (eDNA) in their biofilm matrix that significantly contributes to colonization, persistence, and drug tolerance of these biofilms, suggesting a novel antivirulence target for NTM (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of nontuberculous mycobacteria (NTM) to form biofilm creates challenges for treatment efficacy and host clearance (7, 8, 10, 11). We recently reported that NTM contain extracellular DNA (eDNA) in their biofilm matrix that significantly contributes to colonization, persistence, and drug tolerance of these biofilms, suggesting a novel antivirulence target for NTM (23).…”
Section: Discussionmentioning
confidence: 99%
“…Surveilling macrophages that encounter M. avium subsp. hominissuis biofilm in vitro become hyperstimulated and undergo early, rapid apoptosis in a tumor necrosis alpha (TNF-α)-dependent manner (11), which could explain why the aggregates and biofilms are not cleared by the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Cultures of M. avium complex in with genetically-attenuated biofi lm formation demonstrated reduced invasion of bronchial epithelial cells (Yamazaki et al 2006 ), whereas wild-type M. avium complex biofi lms resisted clearance by, and induced apoptosis in, human mononuclear phagocytes more rapidly than their planktonic cognate (Rose and Bermudez 2014 ). Curiously, M. abscessus biofi lms were signifi cantly enhanced in the presence of necrotic neutrophils, an environment mimicking the namesake clinical syndrome caused by M. abscessus (Malcolm et al 2013 ).…”
Section: Biofi Lms In Clinical Isolates Of Mycobacterium Sppmentioning
confidence: 93%
“…In the present study, we have adopted a quantitative proteomics-based approach to gain insight into the reprogramming of the THP-1 cell line, an acute monocytic leukemia-derived human cell line, exposed to L. donovani for different time periods. Activated THP-1 cells have long been used as a versatile model system to study inflammatory responses, host cell apoptosis, and autophagy behavior in response to intracellular pathogens (16,17). This model may not completely replicate the in vivo conditions after infection, but it is a well-established in vitro model system to study the host-Leishmania interface (18).…”
mentioning
confidence: 99%